The Macroeconomic and Fiscal Impact of Aging in Thailand - Bandaogo, Mahama (World Bank, Washington, DC, 2021)
This paper contributes to the existing literature in several ways. First of all, to the best of our knowledge this is the first paper to exclusively model and analyze the impact of aging on long-term growth in Thailand. Although there several studies that have analyzed the relationship between aging and private saving in Thailand, this is the first to employ a cointegration analysis. This approach is more suitable given that we are interested in the long-term relationship between the two and the fact that demographic changes are slow. Moreover, this paper is the first most comprehensive study of the macroeconomic and fiscal impacts of aging in Thailand. Existing studies have focused on how aging impacts one variable (Pootrakool et al. 2005; IMF 2019). The rest of this paper is organized as follows. Section two presents an assessment of the impact of aging on macroeconomic variables. Section three analyzes how aging is likely to impact Thailand’s fiscal standing. Section four discusses various reforms that can help mitigate the negative impact of aging on long-term growth and fiscal sustainability and section five concludes.